“MAGICAL ELEMENTS OF ENGLISH AND UZBEK FAIRY TALES” (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article explores the magical elements  in English and Uzbek fairy tales, comparing and contrasting the use of fantastical elements in these two cultural traditions. By analyzing a selection of fairy tales from both languages folklore, the study explores  the themes, motifs, and symbolism of magic within these narratives.